PENGARUH PERUBAHAN PREFRENSI MAKANAN DAN DAMPAK TREN KULINER TERHADAP MINAT BELI MAKANAN TRADISIONAL GENERASI Z DI JAKARTA - Ellen Erlanda; Antonius Rizki Krisnadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The rapid development of the culinary industry in the era of globalization has impacted changes in consumer patterns, particularly among Generation Z, who are heavily influenced by modern culinary trends and social media. This phenomenon poses challenges for the sustainability of traditional foods, which are increasingly less favored due to shifting consumption preferences. This study aims to analyze the influence of changes in food preferences and the impact of culinary trends on Generation Z's purchasing interest in traditional foods in Jakarta. This study employs a quantitative method with a population of Generation Z aged 18–28 years who have purchased traditional Jakarta-style food. The sample was selected using purposive sampling with the Slovin formula, resulting in 100 respondents. Data collection was conducted through the distribution of a Likert-scale questionnaire, while data analysis utilized multiple linear regression analysis assisted by SPSS software. The validity and reliability tests showed that the research instruments were valid and reliable. The T-test indicated that changes in food preferences and culinary trends significantly influenced purchasing interest in traditional food, with calculated t-values of 5.742 and 4.940, respectively, which were greater than the critical t-value of 1.984, and a significance level of 0.000 < 0.05. The F test also showed the simultaneous influence of both independent variables with an F value of 46.501, which is greater than the F table value of 3.09. These findings prove that Generation Z tends to be interested in culinary innovations that combine elements of traditional food authenticity with modern culinary trends that are visually appealing and viral on social media. This study is expected to serve as a reference for strategies to preserve traditional food through adaptive innovation.